A systematic review of training methods to increase staff's knowledge and implementation of positive behaviour support in residential and day settings for individuals with intellectual and developmental disabilities. (September 2022) - Mahon, Dearbaile; Walsh, Edith; Holloway, Jennifer; Lydon, Helena
Behaviour support plans (BSPs), if accurately implemented, have been found to increase skills and decrease challenging behaviour of individuals with intellectual and developmental disabilities. Training is essential for staff to acquire the skills necessary for accurate implementation. The aim of this systematic literature review was to evaluate procedures used to train staff in Positive Behaviour Support (PBS), on both knowledge of PBS and implementation of BSPs. Systematic searches of 4 databases identified 18 studies as meeting criteria. Findings indicate that description alone was not consistently effective in increasing knowledge and should be used in combination with other training strategies. Staff's implementation of BSPs were increased by different combinations of the following training components: description, feedback, modelling, role-play, monitory incentive, and escape contingency. To identify evidenced based practice when training staff on BSPs, it is necessary to evaluate active and feasible training components from current training models.